Intragenic Deletions in FLNB Are Part of the Mutational Spectrum Causing Spondylocarpotarsal Synostosis Syndrome - Fukushima, Kaya (Genes (Basel), 2021)
Spondylocarpotarsal synostosis syndrome (SCT) is characterized by vertebral fusions, a disproportionately short stature, and synostosis of carpal and tarsal bones. Pathogenic variants in FLNB, MYH3, and possibly in RFLNA, have been reported to be responsible for this condition. Here, we present two unrelated individuals presenting with features typical of SCT in which Sanger sequencing combined with whole genome sequencing identified novel, homozygous intragenic deletions in FLNB (c.1346-1372_1941+389del and c.3127-353_4223-1836del). Both deletions remove several consecutive exons and are predicted to result in a frameshift. To our knowledge, this is the first time that large structural variants in FLNB have been reported in SCT, and thus our findings add to the classes of variation that can lead to this disorder. These cases highlight the need for copy number sensitive methods to be utilized in order to be comprehensive in the search for a molecular diagnosis in individuals with a clinical diagnosis of SCT.